Welfare Schemes for Agricultural Labourers: A Multidimensional Analysis - Fathimabi P K (Department of Agricultural Extension, College of Agriculture, 1993)
The study, ‘Welfare Schemes for Agricultural Labourers – A Multidimensional Analysis’ was carried out with the following objectives. 1. To study the characteristic profile of agricultural labourers under KAWPS and KAWWFS. 2. To study the awareness of agricultural labourers about the modus operandi of KAWPS and KAWWFS. 3. To study the attitude of agricultural labourers towards KAWPS and KAWWFS. 4. To study the utility perception of agricultural labourers about KAWPS and KAWWFS. 5. To study the attitude of implementing officials towards KAWPS and KAWWFS. 6. To identify the constraints if any, experienced by agricultural labourers under KAWPS and KAWWFS and by officials in implementing the same. 7. To suggest the ways and means, to improve KAWPS and KAWWFS. The study was conducted in 10 randomly selected panchayats of Thiruvananthapuram district. A sample of 160 agricultural labourers i. e. 80 under KAWPS and 80 under KAWWFS selected using random allocation technique, formed the respondents of the study. In addition to that, 23 officials associated with the implementation of KAWPS and KAWWFS were also included in the present study. Personal interview was conducted with the help of well-structured and pre-tested interview schedule to collect data from agricultural labourers and a structured questionnaire was used to collect data from implementing officials. The analysis of welfare schemes for agricultural labourers was done by studying the awareness, attitude and utility perception of agricultural labourers about KAWPS and KAWWFS which formed the dependent variables of the study. The selected profile characteristics of agricultural labourers were taken as independent variables which included education, family education status, family size, socio-economic status, cosmopoliteness, mass media participation, social participation, contact with extension agency, economic motivation, innovativeness and level of aspiration (both future and present). The salient findings of the study are as follows Majority of agricultural labourers under KAWPS were found to have low education, low family education status, small family size, low socio-economic status, low cosmopoliteness, low mass media participation, low social participation, low contact with extension agency, high economic motivation, high innovativeness and low level of aspiration (both future and present). Majority of agricultural labourers under KAWWFS had high education, high family education status, large family size, high socio-economic status, high cosmopoliteness, low mass media participation, high social participation, low contact with extension agency, high economic motivation, high innovativeness and high level of aspiration (both future and present). Majority of agricultural labourers under KAWPS and KAWWFS had high awareness about modus operandi of KAWPS and KAWWFS respectively. Majority of agricultural labourers under KAWPS and KAWWFS had favourable attitude towards KAWPS and KAWWFS respectively. Majority of agricultural labourers under KAWPS had high utility perception about KAWPS and majority under KAWWFS had low utility perception about KAWWFS. There was significant difference between agricultural labourers under KAWPS and KAWWFS with respect to all their selected profile characteristics. Positive and significant correlation was obtained between awareness of agricultural labourers under KAWPS about modus operandi of KAWPS and their characteristics like education, socio-economic status, cosmopoliteness, mass media participation, social participation, contact with extension agency, innovativeness and level of aspiration (future). Characteristics of agricultural labourers under KAWWFS like education, family size, socio-economic status, cosmopoliteness, mass media participation, social participation, contact with extension agency, economic motivation, innovativeness and level of aspiration (future) were found to have a positive and significant correlation with their awareness about modus operandi of KAWWFS. Level of aspiration (both future and present) of agricultural labourers under KAWPS had negative and significant correlation with their attitude towards KAWPS. Education, cosmopoliteness, mass media participation, contact with extension agency, economic motivation, innovativeness and level of aspiration (future) of agricultural labourers under KAWWFS had positive and significant relationship with their attitude towards KAWWFS. Family size of agricultural labourers under KAWPS had positive and significant correlation with their utility perception about KAWPS. Socio-economic status, cosmopoliteness, mass media participation, social participation, economic motivation, innovativeness and level of aspiration (both future and present) of agricultural labourers under KAWWFS had positive and significant correlation with their utility perception about KAWWFS while education had negative and significant correlation. Majority of the implementing officials had a favourable attitude towards KAWPS and KAWWFS. Most important constraint experienced by agricultural labourers under KAWPS was 'non-availability of pension regularly' while those under KAWWFS was 'non-availability of benefits in time'. 'Identification of agricultural labourer as per the rules and regulations of the scheme' and 'the staff pattern allowed is insufficient' were the most important constraints experienced by officials in the implementation of KAWPS and KAWWFS respectively.